Pengaruh Word Of Mouth, Kualitas Produk Dan Loyalitas Terhadap Keputusan Pembelian Konsumer Readymix Di Kota Batam - Tivano, Nico; Nainggolan, Nora Pitri (Jurnal Ilmiah Wahana Pendidikan, 2024)
Batam, as one of the major cities in Indonesia, with its various policies, undoubtedly attracts significant investments in infrastructure and other sectors to support the city's progress. To facilitate development and strengthen structures, high-quality and trusted Readymix is essential. Therefore, various factors are needed to encourage consumers and investors to make informed decisions in selecting quality Readymix. The objective of this research is to examine the influence of Word Of Mouth, product quality, and Loyalty on the purchasing decisions of Readymix in the city of Batam. This study adopts a quantitative approach, employing a questionnaire as the instrument with 100 respondents from Batam, determined using the Slovin formula. The questionnaire serves as the data collection technique. Data analysis is conducted using SPSS 25, encompassing descriptive statistical tests, data quality tests, classic assumption tests, influence tests, and hypothesis tests. Based on multiple linear regression results, Word Of Mouth (X1) has an influence of 0.097 or 9.7% on purchasing decisions (Y), product quality (X2) has an influence of 0.327 or 32.7% on purchasing decisions (Y), and Loyalty (X3) has an influence of 0.47 or 47% on purchasing decisions (Y). Additionally, Word Of Mouth, Product Quality, and Loyalty collectively have a significant impact on the purchasing decisions of Readymix in Batam, accounting for 0.98 or 98%, as per the coefficient of determination (R2). According to the hypothesis test results, it is also evident that Word Of Mouth, product quality, and Loyalty, both individually and collectively, influence the purchasing decisions of Readymix in Batam.